Towards an effective legal and regulatory framework for Islamic financial transactions Major initiatives of the Central Bank of Malaysia - Engku Ali, Engku Rabiah Adawiah; Oseni, Umar A. (Emerald Publishing Limited, 2017)
Purpose – In propelling Malaysia to become a high value-added and high-income economy by 2020, the Central Bank of Malaysia has consistently emphasized the need for a new trajectory of transformation and growth which will leverage on a robust legal framework that for enhancing Islamic financial transactions. This paper aims to examine the latest major policy initiatives and legal reforms introduced to promote both local and cross-border transactions that seek to project Malaysia as a hub for Islamic financial transactions. Design/methodology/approach – While adopting an analytical approach in analysing the relevant issues, the study relies on doctrinal legal method in highlighting major reforms introduced to enhance the legal and regulatory framework of Islamic finance. Findings – The study finds that the importance of law reforms in strengthening the financial system cannot be overemphasized, particularly when it comes to the need for an end-to-end Sharīʿah compliance framework and consumer protection. Practical implications – Other emerging jurisdictions aspiring to adopt Islamic finance products can learn from the Malaysia’s pioneering role in introducing an effective legal and regulatory framework. Originality/value – Though there are a number of studies on Malaysia’s leading role in the law and regulation of Islamic finance, this study is one of the earliest attempts to explore the role of the Central Bank of Malaysia in enhancing the legal framework for Islamic financial transactions through the introduction of the Islamic Financial Services Act 2013 and other relevant policy regulations.